Mengenal bilangan : belajar bahasa Inggris bersama Franklin / Rosemarie Shannon ; penerjemah, Maria Agustina, Rosalia Emmy ; editor, Flora Maharani, Maria Agustina - SHANNON, Rosemarie; Maria Agustina; Flora Maharani; Rosalia Emmy (Kanisius, 2016)
31 hlm. : ilus. ; 30 cm